The Effect Of Price, Service Quality And Location On Consumer Buying Interest At Ayam Geprek Mbah Roso - Deny Apriani; Bayu Eko Broto; Raja Saol Marto Hendry (Amkop Management Accounting Review (AMAR), 2026)
This study aims to analyze the influence of price, service quality, and location on consumer purchasing intention at Mbah Roso's Ayam Geprek Restaurant, a popular local culinary business among Indonesian consumers. The background of this study is the intense competition in the culinary industry, which encourages the importance of understanding the factors that influence consumer purchasing decisions. This study uses a quantitative approach with a survey research design, where data are collected through questionnaires distributed to 98 respondents. The analysis techniques used include validity tests, reliability tests, classical assumption tests, and multiple linear regression to examine the influence of each variable on consumer purchasing intention. The results of the analysis show that price, service quality, and location have a valid relationship with consumer purchasing intention, but do not show a significant effect either partially or simultaneously. The low R² value (0.028) indicates that the three variables are only able to explain a small part of the variation in consumer purchasing intention. This study contributes to the theory of consumer behavior and marketing mix in the context of local culinary businesses in Indonesia. Practically, the results of this study indicate that the management of Ayam Geprek Mbah Roso Restaurant needs to consider other factors, such as promotions and product innovation, to increase consumer purchasing interest. Future research could expand the scope of the variables studied, including consumer emotional and psychological factors